2018
DOI: 10.14233/ajchem.2018.20979
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification of Waste Cooking Oil Using NH2/MCM-41 Base Catalyst: Effect of Methanol/Oil Mole Ratio and Catalyst/Oil Weight Ratio towards Conversion of Ester

Abstract: Transesterification of waste cooking oil (WCO) using NH2/MCM-41 base catalyst has been carried out. The MCM-41 was synthesized by hydrothermal method using the silica from Sidoarjo mud and cetyltrimethylammonium bromide (CTAB) as a template and calcined at 540 °C for 5 h. The MCM-41 was modified by adding (3-aminopropyl) trimethoxysilane using 5 mol percent of N/Si to produce NH2/MCM-41 base catalyst. Transesterification of waste cooking oil was carried out under variation of methanol/WCO mole ratio of 6, 9, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The metal content of the samples was analyzed by X-ray Fluorescence (XRF, PANalytical MiPal 4). In general, the absorption band (Si-OH) and siloxane groups (Si it can be repeated the application of silica extraction methods according to what has been previous researchers 17,18 . The interpretation of the FTIR result shows silica successfully extracted from the mud as it had a functional group typical of silica.…”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal content of the samples was analyzed by X-ray Fluorescence (XRF, PANalytical MiPal 4). In general, the absorption band (Si-OH) and siloxane groups (Si it can be repeated the application of silica extraction methods according to what has been previous researchers 17,18 . The interpretation of the FTIR result shows silica successfully extracted from the mud as it had a functional group typical of silica.…”
Section: Detection Methodsmentioning
confidence: 99%
“…The extraction of silica was accomplished according to Triyono et al research 17 . The Sidoarjo mud was cleaned and washed with aquadest and dried.…”
Section: Extraction Of Silica From Sidoarjo Mudmentioning
confidence: 99%
“…111 In the same study, SBA-15COOH and SBA-15NH 2 were tested for the removal of dyes, an application that had already been well documented. [112][113][114][115] The functionalization of silanol groups of OMS with NH 2 , COOH and SH [116][117][118][119][120][121] has allowed for the coupling of organic dyes to obtain a photocatalytic material able to catalyze different reactions 73,[122][123][124][125] (Fig. 3).…”
Section: Ordered Mesoporous Silica (Oms)mentioning
confidence: 99%
“…Aminated MCM-41 are interesting catalysts from an industrial perspective given the stability and intrinsic reusability of these particles. Recently, Trisunaryanti et al [13] reported the use of NH 2 -MCM-41 in the transesterification of vegetable oils to prepare biodiesel fuel from waste cooking oil. In the same work, the reaction conditions were optimized.…”
Section: Amino Functionalization: Nh 2 -Mcm-41mentioning
confidence: 99%